Transformational leadership and its relationship to organizational creativity in Algerian sports federations - Falah , Hicham; Laoucine, slimane (sports creativity, 2025)
It is considered .The present study is conducted with the objective of exploring the relationship between transformational leadership and organizational culture in the Algerian sports associations–Federation sports federations of wrestling ;taekwondo ;sports university ;- By practicing the transformational leadership at the level of the federations management in its multiple dimensions In order to achieve the objective of this study, two research instruments are used following a quantitative, qualitative and a descriptive approach. The study sample consists of 18 individuals. The analysis of the findings shows that there is a positive statistical correlation between transformational leadership and creativity level of organization among a range wide of staff employees at the federations